Gene Body Methylation Patterns in Daphnia Are Associated with Gene Family Size - Asselman, Jana (Genome Biol Evol, 2016)
The relation between gene body methylation and gene function remains elusive. Yet, our understanding of this relationship can contribute significant knowledge on how and why organisms target specific gene bodies for methylation. Here, we studied gene body methylation patterns in two Daphnia species. We observed both highly methylated genes and genes devoid of methylation in a background of low global methylation levels. A small but highly significant number of genes was highly methylated in both species. Remarkably, functional analyses indicate that variation in methylation within and between Daphnia species is primarily targeted to small gene families whereas large gene families tend to lack variation. The degree of sequence similarity could not explain the observed pattern. Furthermore, a significant negative correlation between gene family size and the degree of methylation suggests that gene body methylation may help regulate gene family expansion and functional diversification of gene families leading to phenotypic variation.